2019
DOI: 10.1007/s13167-018-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and tooth regeneration: prospects for personalized dentistry

Abstract: Over the last several decades, a wealth of information has become available regarding various sources of stem cells and their potential use for regenerative purposes. Given the intense debate regarding embryonic stem cells, much of the focus has centered around application of adult stem cells for regenerative engineering along with other relevant aspects including use of growth factors and scaffolding materials. The more recent discovery of tooth-derived stem cells has sparked much interest in their applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 61 publications
0
17
0
4
Order By: Relevance
“…Стовбурові клітини -це незрілі клітини, які характеризуються високим потенціалом проліферації та диференціації за різними клітинними лініями залежно від сигналів внутрішнього та зовнішнього біологічного середовища. Ці неспеціалізовані клітини мають дві важливі характеристики: по-перше, вони здатні до самостійного відновлення шляхом поділу клітин навіть після тривалих періодів призупиненого поділу генетичними сигналами, по-друге, за певних фізіологічних чи експериментальних умов вони можуть утворювати функціональні клітини тієї чи іншої тканини або органу [4].…”
Section: Discussionunclassified
“…Стовбурові клітини -це незрілі клітини, які характеризуються високим потенціалом проліферації та диференціації за різними клітинними лініями залежно від сигналів внутрішнього та зовнішнього біологічного середовища. Ці неспеціалізовані клітини мають дві важливі характеристики: по-перше, вони здатні до самостійного відновлення шляхом поділу клітин навіть після тривалих періодів призупиненого поділу генетичними сигналами, по-друге, за певних фізіологічних чи експериментальних умов вони можуть утворювати функціональні клітини тієї чи іншої тканини або органу [4].…”
Section: Discussionunclassified
“…However, these materials are not capable of replacing biological functions of lost tissue, leading to the reduced mechanical properties and reduced vitality of the teeth. Therefore, stem cell-based therapies would be an improving approach to repair or replace the damaged or lost tissues of teeth in order to recover the morphological and biological functions [ 204 ]. Recently, it was shown that UC-MSC possess the ability to differentiate into odontoblast-like cells under the microenvironment induced by a liquid extract of human treated dentin matrix in vitro [ 205 ].…”
Section: New Horizons For Clinical Applications Of Mscmentioning
confidence: 99%
“…They can be isolated from a wide variety of tissues, including dental tissues. They can renew themselves and differentiate under stimulation to yield some specialized cell types 10 …”
Section: Introductionmentioning
confidence: 99%